Analyzing the effects of airfield resources on airlift capacity - Stucker, J. P.; Williams, Laura Melody; Rand Corporation; National Defense Research Institute (U.S.). Forces and Resources Policy Center; United States. Department of Defense. Office of the Secretary of Defense (Santa Monica, CA : RAND, 1999)
This research investigated how differing levels and distributions of airfield resources can affect the quantity of airlift deliveries. Specifically, the study demonstrates the combined use of two models to improve and facilitate the analysis of the effects of airfield resources on airlift performance. One model is ACE (Airfield Capacity Estimator), a relatively high-resolution model of airfield resources and operations; the other is NRMO (Naval Postgraduate School/RAND Mobility Optimization), a large-scale linear-programming model of military airlift. Using a scenario provided by the Air Force's Air Mobility Command (AMC) of a major war in Southwest Asia, the RAND analysts showed how ACE and NRMO together could complement AMC's models and analyses and how the ACE/NRMO estimates might expand or validate those of AMC. The study validated AMC's conclusion that the current European en route infrastructure would significantly constrain deliveries of major cargoes during a major deployment to Southwest Asia. Both RAND and AMC estimated that current en route resource shortages would reduce cargo deliveries by roughly 20 percent from what they could be if those shortages did not exist. Moreover, the study expanded AMC's findings (a) by demonstrating the sensitivity of deliveries to assumptions concerning aircraft ground times at the on-load, en route, and off-load airfields and (b) by demonstrating how a better distribution of existing en route resources could significantly increase the amount of cargo delivered during the first 30 days of the conflict. The study illustrates that ACE and NRMO can augment the strategic mobility analyses needed by the Office of the Secretary of Defense and others by detecting capabilities and providing insights that are not available from other models. The report should be of interest to deployment planners and to air mobility resource programmers and managers.
"National Defense Research Institute."
Includes bibliographical references (p. 81).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Airlift, Military -- United States; Airports -- United States -- Traffic control